Stromal-epithelial interaction induces GALNT14 in prostate carcinoma cells - Czyrnik, Elena D.; Wiesehöfer, Marc; Dankert, Jaroslaw T.; Wach, Sven; Wagner, Mathias; Spahn, Martin; Kruithof de Julio, Marianna; Wennemuth, Gunther (Frontiers in Oncology, 2023)
Cell-cell communication is an important process in healthy tissue but also gains enhanced attention regarding pathological tissue. To date, the tumor microenvironment is gradually brought into focus when studying tumorigenesis. In the prostate gland, stromal and epithelial cells greatly interact to maintain homeostasis or tissue integrity. This study focuses on an indirect communication via soluble factors. To investigate the cell-cell interaction via soluble factors, the prostate carcinoma cell line LNCaP and the stromal primary cells p21 were co-cultured without direct contact and RNA was isolated at defined time points. Differences in gene expression were finally analyzed by RNA sequencing. RNA sequencing revealed a time-depending differential expression profile. Selected factors were subsequently characterized at molecular level and analyzed in human prostate tissue of different developmental stages as well as pathology. GALNT14 was one of the highest induced co-culture-specific genes in LNCaP cells. Detection in healthy tissue and BPH revealed an age-dependent decrease in GALNT14 expression. Moreover, in prostate carcinoma, GALNT14 expression heavily varied independent of the Gleason score. Overall, this work provides a basis for further studies related to paracrine stromal-epithelial interaction in prostate carcinoma and highlights the importance of GALNT14.